Teaching Medical Students to work with Interpreters - Sandra Hale, Elizabeth Friedman-Rhodes (The Journal of Specialised Translation, 2010)
Research into Medical Interpreting seems to indicate that there is little understanding of the role of the interpreter and of the interpreting process among medical practitioners. It has been argued that such a situation can lead to negative consequences for the doctor-patient relationship and therefore affect health outcomes (Cambridge, 1999; Tebble 1999; Davidson, 2000; Bischoff, 2003; Angelelli, 2004; Hale, 2007). This paper will present the results of a small case study which aimed to ascertain the perceptions held by first year medical students about interpreters and the interpreting process, and test the effectiveness of a three-hour workshop on working with interpreters. The results indicate that after the workshop students became more aware of the linguistic complexities involved in interpreting, increased their awareness of the need to only work with trained interpreters and improved their understanding of the meaning of accuracy and the role of the interpreter.